The deadline : essays - Lepore, Jill, 1966- (Liveright Publishing Corporation, a division of W.W. Norton & Company, 2023)
Few, if any, historians have brought such insight, wisdom, and empathy to public discourse as Jill Lepore. Arriving at The New Yorker in 2005, Lepore, with her panoptical range and razor-sharp style, brought a transporting freshness and a literary vivacity to everything from profiles of long-dead writers to urgent constitutional analysis to an unsparing scrutiny of the woeful affairs of the nation itself. The astonishing essays collected in The Deadline offer a prismatic portrait of Americans' techno-utopianism, frantic fractiousness, and unprecedented--but armed--aimlessness. From lockdowns and race commissions to Bratz dolls and bicycles, to the losses that haunt Lepore's life, these essays again and again cross what she calls the deadline, the "river of time that divides the quick from the dead." Echoing Gore Vidal's United States in its massive intellectual erudition, The Deadline, with its remarkable juxtaposition of the political and the personal, challenges the very nature of the essay--and of history--itself.--